Syariat dan Reformasi Hukum di Indonesia Kontemporer - Taufik Adnan Amal (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
Book Review: Nadirsyah Hosen, Shari'a and Constitutional Reform in lndonesia Singapore: Institute of Southeast Asian Studies [ISEAS], Singapore, 2007; x + 271pp., bibliografi, indeksThis book clearly provides a valuable contribution to theory regarding constitutional reformation in Indonesia and the relevance of Islamic law institutions. This book is not only important for understanding political movements seeking to strengthen the role of Islam in the political and social sphere in Indonesia, but it is also significant for studies about the inclusion of aspects of Islamic law in the Constitution. For this reason, this book is certainly a must read for those studying-or simply interested in-the field of constitutional reform and law in IndonesiaDOI: 10.15408/sdi.v15i1.540